Investigation of the Stock Structure of Atlantic Walrus (Odobenus rosmarus rosmarus) in Canada and Greenland Using Dental Pb Isotopes Derived from Local Geochemical Environments - Outridge, P.M.; Davis, W.J.; Stewart, R.E.A.; Born, E.W. (ARCTIC, 2003)
The chemical composition of animal tissues such as teeth appears to reflect an individual's exposure to its geochemical environment. In this study, the lead (Pb) isotope composition of dental cementum was used to investigate the stock structure of Atlantic walrus (Odobenus rosmarus rosmarus) in the Canadian Arctic and Greenland. The 12 communities providing walrus samples for this study represent most of the Canadian and Greenlandic villages where walrus still form an important part of the traditional Inuit diet. Significant differences between locations in mean Pb isotope ratios and the limited overlap of the ranges of values indicate that each village harvested walrus herds that exploited substantially different geological/geographical habitats. This geographic segregation based on isotopic signatures suggests that most walrus stocks (i.e., the groups of walrus that interact with hunters at each community) are more localized in their range than previously thought. 208Pb/207Pb and 208Pb/204Pb were the most important stock discriminators, reflecting the influence of local geological Th/U composition (i.e., 208Pb) on Pb isotope composition in walrus teeth. 204Pb-based isotope ratios in walrus were consistently higher (more radiogenic) and more homogeneous than those in regional terrestrial bedrock, a difference probably due to selective leaching of radiogenic Pb from mineral phases into seawater and mixing during weathering and transport. Dental Pb isotope signatures may have widespread application to stock discrimination of other coastal marine mammal species. La composition chimique de tissus animaux tels que les dents semble refléter l'exposition d'un individu à son milieu géochimique. Pour la présente étude, on a utilisé la composition isotopique du plomb (Pb) contenu dans le cément pour examiner la structure du stock du morse de l'Atlantique (Odobenus rosmarus rosmarus) dans l'Arctique canadien et le Groenland. Les 12 communautés qui ont fourni les échantillons de morse pour ce projet représentent la ...